High performance computing and grids in action - Grandinetti, Lucio, 1941- (Advances in parallel computing, 2008)
Collects in four chapters single monographs related to the fundamental advances in parallel computer systems and their developments from different points of view (from computer scientists, computer manufacturers, end users) and related to the establishment and evolution of grids fundamentals, implementation and deployment.